Methods of Reducing Waste after Grape Harvest - Muhammadi, Muhammad Roki (Journal of Natural Sciences – Kabul University, 2024)
Grapes are the largest agricultural product of Afghanistan. Grapes contain 79% water, 14% different sugars, mineral salts and a set of beneficial elements and compounds. Grapes have vitamins A, B, C, D. (Roshan et al.) The waste of agricultural products is one of the serious challenges of most countries, especially developing countries. This article, which has been compiled using library documents and research articles, has investigated the methods of reducing waste after harvest of grapes, which plays an important role in reducing waste after harvest, maintaining quality, creating employment, and providing self-sufficiency. Fruits are among the most important products that play an important role in providing human nutrition. These types of products are susceptible to spoilage due to having a lot of water, and during the post-harvest period, a major part of them (between 5 and 50%) is destroyed. Harvesting operations, moving the product in the field, carrying and transporting have a large role in post-harvest rotting and losses in fruits. Mechanical damage to the product during harvesting and after, physiological and environmental factors and contamination by microbial and biological agents are the most important causes of post-harvest losses in fruits and vegetables. In order to reduce the waste after harvesting of grapes, various strategies can be used, such as proper nutrition and agricultural operations before harvesting, appropriate operations during harvesting and appropriate operations after harvesting, such as initial cooling and removing heat from the field, using clean and suitable equipment, suitable packaging. It was considered to store and transfer to the market.